Deep eutectic solvent plasticization of chitosan/distiller's grains prolamin films: Hydrogen bond-driven structural regulation and enhanced food preservation performance - Lin Deng; Haoyang Sun; Xiaomeng Li; Yi Sun; Yarong Wang; Hongyu Yang; Jian Su; Long Sheng; Jia Zheng; Zhaoxia Cai (Food Research International, 2026)

Nanoconfined iron-based catalysts activate peroxymonosulfate via electron transfer and radical pathways for efficient bisphenol A removal - Mingyu Sun; Qingqing Hao; Jingxingyu Wu; Chenye Fu; Long Lin; Guochun Lv; Shihuai Deng; Xiaohui Lu; Jiali Peng (Journal of Hazardous Materials, 2026)

Corrigendum to “Calcium isotopic signatures of mid-ocean ridge basalts from the eastern Galápagos Spreading Center that influenced by plume-ridge interaction” [Chemical Geology 715 (2026) 123478] - Yujie Shan; Renqiang Liao; Peijun Lin; Jianghong Deng; Long Du; Xin Li; Hongli Zhu; Zhaofeng Zhang; Weidong Sun (Chemical Geology, 2026)

Urea-melamine-derived nitrogen-doped biochar flow electrodes for enhanced treatment of nickel-containing electroplating wastewater - Jian Peng; Ziyi Deng; Wei Liu; Hande Zhang; Yangxiong Huang; Ruixiong Huang; Rikun Lai; Yong Yang; Jianyou Long; Wubiao Lin; Jie Shu; Huosheng Li (Journal of Environmental Chemical Engineering, 2026)

Calcium isotopic signatures of mid-ocean ridge basalts from the eastern Galápagos Spreading Center that influenced by plume-ridge interaction - Yujie Shan; Renqiang Liao; Peijun Lin; Jianghong Deng; Long Du; Xin Li; Hongli Zhu; Zhaofeng Zhang; Weidong Sun (Chemical Geology, 2026)

Fluorescence spectroscopy coupled with machine learning for identification of recycled PET - Ze-Long Deng; Qing-Hua Yang; Qi-Zhi Su; Xue-Chao Song; Qin-Bao Lin (Food Packaging and Shelf Life, 2026)

Microplastic entry into bloodstream via hemodialysis: A dual-simulation clinical study - Yao Deng; Taoping Sun; Zhenheng Long; Xiaoling Luo; Xuyang Geng; Zefang Lin; Chunzhao Chen; Xiaoliang Li (Environmental Pollution, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

Enhanced pollutant removal via polybutylene succinate-based microbial-agent biofilm process: Optimizing heterotrophic nitrification–aerobic denitrification technology for low-carbon wastewater treatment - Qian Zhang; Zheng Chen; Kun Long; Bixiang Nie; Fu Wei; Lin Deng; Siyu Hua (Journal of Environmental Chemical Engineering, 2026)

Regulation of solubility and thermal stability for egg white proteins via alkaline heat treatment: A new insight into protein conformation and interactions at the nanoscale - Xiaomeng Li; Wei Hu; Lingzhuo Li; Mohamed Salama; Jieling Chen; Lin Deng; Long sheng; Zhaoxia Cai (Food Chemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Neglected thermal effects of color-temperature on algal growth in aquatic environment under light - Guijiao Lin; Kaikai Deng; Peng Yan; Hao Yang; Bin Chen; Qiang He; Dongling Long; Jinsong Guo (Water Research, 2025)

A new exhalative sedimentary metallogenetic model for Permian manganese deposits in China - Zhichen Liu; Yu Liu; Sui Zhang; Lin Xiao; Jianxi Long; Deng Chen; Yang Wang; Zequan Wei; Yi Zheng; Liang Xiao (Journal of Asian Earth Sciences, 2025)

Enhanced heat transfer and flow dynamics in liquid helium-free MRI cooling devices: A physical-based modeling approach - Changhao Luo; Zhiqiang Long; Yi Deng; Guanhua Liu; Meng Lin (International Journal of Refrigeration, 2025)

Complete nitrogen removal via novel nitrite-absent anodic anammox process with granular sludge in titanium anode microbial electrolysis cells - Liang Zhu; Jingwei Ma; Zhanhang Wang; Ying Han; Long Chen; Hui Sun; Qiulai He; Lin Deng; Zhou Shi; Shuizhou Ke (Chemical Engineering Journal, 2025)

A new illudane sesquiterpene from the edible fungus Pholiota nameko - Lian Yang; Huan Zhang; Shu-Hang He; Ju Xu; Xiao-Long Li; Fei-Xing Li; Dong-Mei Lin; Deng-Ji Lou; Xiao-Yan Yang (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Mechanistic insights into the chlorination volatilization of oxidized heavy metals via novel staggered chlorination roasting - Chenglong Lu; Xuan Yu; Guohao Yang; Qianqian Guo; Long Jiao; Jinxiang Lin; Kai Deng; Yanjun Hu (Waste Disposal & Sustainable Energy, 2025)

Genetic identification and characterization of quantitative trait loci for wheat grain size-related traits independent of grain number per spike - Tao Li; Yanyan Tang; ZhengXi Lin; Jinghui Wang; Juanyu Zhang; Qiang Li; Furong Huang; Junjun Liang; Haili Zhang; Zehou Liu; Jun Li; Wuyun Yang; et al. (Theoretical and Applied Genetics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Recent advances in iron-based catalyst-driven persulfate activation for organic pollutant degradation - Huawen Hu; Jin Liu; Xiyu Zheng; Kai Zhao; Yinlei Lin; Xuejun Xu; Hangyu Long; Yuyuan Zhang; Xiaowen Wang; Dongchu Chen; Qianjun Deng (Journal of Water Process Engineering, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Degradation of ofloxacin by activation of persulfate with metal-N co-doped modified peanut shell biochar: The key role of cobalt doping - Wei Qian; Yi-Li Deng; Xiao-Long Liu; Hui Liu; Mao-You Ye; Ying-Ying Li; Yong-Zheng Zhang; Zeng-Hui Diao; Jia-Lin Liang (Journal of Water Process Engineering, 2025)

Transcriptome analysis of tilapia streptococcus agalactiae in response to baicalin - Qing-Qin Huang; Shao-Long Liu; Ji-Hui Huang; Fei Wang; Zi-Chen Zhao; Heng-Wei Deng; Chuan Lin; Wei-Liang Guo; Zhi-Hong Zhong; Jian-Long Li; Dong-Dong Zhang; Shi-Feng Wang; et al. (Genes & Genomics, 2025)

Chronology and geofluids characteristics of calcite cement in the Upper Triassic Xujiahe Formation tight sandstone reservoir, Western Sichuan Basin, SW China - Jianchao Zheng; Liangbiao Lin; Yu Yu; Qian Yuan; Long Wen; Xiang Deng; Yi Huang; Yuchao Qiu; Jiaqi Wei; Chao Zheng; Fanchi Nan (Marine and Petroleum Geology, 2024)

Concentric Compressive Behavior and Design of Stainless Steel–Concrete Double-Skin Composite Tubes Influenced by Dual Hydraulic Pressures - Jian-Tao Wang; Yang Yang; Kai-Lin Yang; Deng-Long Hu; Long-Bo Xu; Jun-Xin Li (Journal of Marine Science and Engineering, 2024)
The external hydraulic pressure and internal medium pressure acting on submarine pipelines can lead to the coupling effect of active and passive constraints on the mechanical performance of steel–concrete double-skin composite tubes, resulting in a significantly different bearing capacity mechanism compared to terrestrial engineering. In this paper, the full-range concentric compressive mechanism of new-type stainless steel–concrete double-skin (SSCDS) composite tubes subjected to dual hydraulic pressure was analyzed by the finite element method. The influence of geometric–physical parameters at various water depths was discussed. The key results reveal that imposing dual hydraulic pressures significantly improves the confinement of double-skin tubes to encased concrete, resulting in a higher axial compressive strength and a non-uniform stress distribution; increasing the material strengths of concrete, outer tubes and inner tubes results in an approximately linear enhancement in axial bearing capacity; enhancing the diameter-to-thickness ratios of outer tubes and inner tubes can decrease the bearing capacity of SSCDS composite tubes; and the axial compression strength of SSCDS composite tubes with a higher hollow ratio of 0.849 tends to decrease with increasing outer hydraulic pressure. A practical method that integrates the effects of dual hydraulic pressures was developed and validated for the strength calculation of SSCDS composite tubes. This research provides fundamental guidelines for the application of pipe-in-pipe structures in deep-sea engineering.

Rock abrasiveness prediction based on multi-source physical, mechanical and mineralogical properties - Yun Wu; Long-Chuan Deng; Xiao-Zhao Li; Li-Yuan Yu; Jiang-Feng Liu; Jian Lin (Bulletin of Engineering Geology and the Environment, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Multifunctional self-assembled adsorption microspheres based on waste bamboo shoot shells for multi-pollutant water purification - Jie Yang; Qianxin Long; Yan Zhu; Cheng Lin; Xiaoxi Xu; Baiyang Pan; Wenya Shi; Yuyang Guo; Jianqiu Deng; Qingrong Yao; Zhongmin Wang (Environmental Research, 2024)

Characteristics of energy distribution for N, P and C sequestration by Microcystis aeruginosa under blue and orange light - Dong-ling Long; Gui-jiao Lin; Peng Yan; Hao Yang; Kai-kai Deng; Jin-song Guo (Journal of Environmental Chemical Engineering, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

A functional carbon dots induce ferroptosis by suppressing PLPP4 activity to inhibit glioblastoma growth - Kun Deng; Lianglin Zhang; Wei Gao; Xiang Lin; Xinmiao Long; Yang Wang; Minghua Wu (Chemical Engineering Journal, 2023)

High-level production of cordycepin by the xylose-utilising Cordyceps militaris strain 147 in an optimised medium - Liangkun Long; Zhen Liu; Yizhou Wang; Qunying Lin; Shaojun Ding; Chuanhua Li; Chunying Deng (Bioresource Technology, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Contaminant characterization at pesticide production sites in the Yangtze River Delta: Residue, distribution, and environmental risk - Mei Li; Qiang Chen; Lu Yang; Ya Zhang; Jinlin Jiang; Shaopo Deng; Jinzhong Wan; Tingting Fan; Tao Long; Shengtian Zhang; Yusuo Lin (Science of The Total Environment, 2023)

Release of Endogenous Brain-derived Neurotrophic Factor into the Lateral Entorhinal Cortex from the Paraventricular Thalamus Ameliorates Social Memory Deficits in a Mouse Model of Alzheimer’s Disease - Yun-Long Xu; Lin Zhu; Zi-Jun Chen; Xiao-Fei Deng; Pei-Dong Liu; Shan Li; Bing-Chun Lin; Chuan-Zhong Yang; Wei Xu; Kui-Kui Zhou; Ying-Jie Zhu (Neuroscience Bulletin, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Age- and Nicotine-Associated Gene Expression Changes in the Hippocampus of APP/PS1 Mice - Jie Yang; Yan Long; De-Mei Xu; Bing-Lin Zhu; Xiao-Juan Deng; Zhen Yan; Fei Sun; Guo-Jun Chen (Journal of Molecular Neuroscience, 2019)

Heavy metal distribution, translocation, and human health risk assessment in the soil-rice system around Dongting Lake area, China - Lin Tang; Sihan Deng; Di Tan; Jiumei Long; Ming Lei (Environmental Science and Pollution Research, 2019)

Effects of intercropping with Bidens species plants on the growth and cadmium accumulation of Ziziphus acidojujuba seedlings - Qian Deng; Qunxian Deng; Yang Wang; Lei Li; Xingyu Long; Si Ren; Yue Fan; Lijin Lin; Hui Xia; Dong Liang; Jin Wang; Huifen Zhang; et al. (Environmental Monitoring and Assessment, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Two new alkylated furan derivatives with antifungal and antibacterial activities from the plant endophytic fungus Emericella sp. XL029 - Xia Wu; Xue-Jiao Pang; Lu-Lin Xu; Ting Zhao; Xin-Yu Long; Qiong-Yin Zhang; Hai-Li Qin; Deng-Feng Yang; Xiao-Long Yang (Natural Product Research, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Functional relevance for multiple sclerosis-associated genetic variants - Xiang Lin; Fei-Yan Deng; Xing-Bo Mo; Long-Fei Wu; Shu-Feng Lei (Immunogenetics, 2015)

Critical mechanisms for the formation of extreme arctic sea-ice extent in the summers of 2007 and 1996 - Xiquan Dong; Behnjamin J. Zib; Baike Xi; Ryan Stanfield; Yi Deng; Xiangdong Zhang; Bing Lin; Charles N. Long (Climate Dynamics, 2014)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Molecular tagging of a stripe rust resistance gene in Aegilops tauschii - Lin Huang; Lian-Quan Zhang; Bao-Long Liu; Ze-Hong Yan; Bo Zhang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Euphytica, 2011)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)